(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The Upper Cambrian-Tremadocian rocks exposed in the Alfarcito area of Cordillera Oriental, northwest Argentina reveal a series of transgressive-regressive cycles punctuated by incision of fluvio-estuarine valleys. An integrated sedimentologic, biostratigraphic and sequence stratigraphic study permits characterization of the sedimentary facies and stratal stacking patterns, and a revision of the stratigraphic framework of this succession. The Upper Cambrian-Tremadocian succession is included within the existing Santa Rosita Formation, which is formally subdivided here into six units, the Tilcara, Casa Colorada, Pico de Halcón, Alfarcito, Rupasca and Humacha members. This scheme recognizes the internal complexities of the formation, in that the Tilcara and Pico de Halcón members record sedimentation in areally-restricted incised valleys and contain structures indicative of tidal dominance, whereas the Casa Colorada, Alfarcito and Rupasca members typify wave-dominated open-marine environments, where background suspension-fallout was punctuated by oscillatory flows during storms. The Tilcara Member is incised into the underlying Mesón Group. The Casa Colorada Member reflects a basinwide Late Cambrian transgression and subsequent progradation and consists of lower to upper offshore deposits. The Pico de Halcón Member is incised into the Casa Colorada Member. The Alfarcito Member is divided into three distinctly upward-coarsening and-thickening intervals. The sandstone-dominated intervals are composed of lower to middle shoreface deposits with minor amounts of offshore transition and upper shoreface deposits. The heterolithic, fine-grained intervals record more distal deposition, ranging from the lower offshore to the offshore transition. The Rupasca Member is a dominantly fine-grained unit that records a major late early to early late Tremadocian transgression. The lower interval of this member consists of lower offshore to offshore-transition deposits, while the upper part is made up of shelf to lower offshore deposits. The Humacha Member is not exposed in the study area. The importance of integrating biostratigraphy within a sedimentologic and sequence-stratigraphic framework is underscored here, in that it enables us to construct a more accurate stratigraphic framework which permits a clear understanding of the sedimentary dynamics of this system.